2020
DOI: 10.1002/jmv.25911
|View full text |Cite
|
Sign up to set email alerts
|

CD4/CD8 ratio, comorbidities, and aging in treated HIV infected individuals on viral suppression

Abstract: The progression of the human immunodeficiency virus (HIV) infection to acquired immunodeficiency syndrome (AIDS) can be efficiently interrupted by antiretroviral therapy (ART). However, even successfully treated HIV‐infected individuals are prone to develop non‐AIDS‐related diseases that affect the metabolism and several organs and systems. Biomarkers that predict the occurrence of comorbidities may help develop preventive measures. Current research shows that CD4+ T cell counts and viral load do not predict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
(77 reference statements)
1
10
0
3
Order By: Relevance
“…Verificou-se que os níveis de linfócitos T CD8 + estavam diretamente relacionados a carga viral e isso deve-se ao importante papel dessas células no combate às infecções causadas por vírus. Portanto, na tentativa de eliminar o vírus, quanto maior a carga viral, maiores serão os níveis detectados dessas células 1,25 . As células T CD4 + , por sua vez, apresentaram uma relação inversamente proporcional com a carga viral, o que pode ser justificada pela história natural da infecção pelo HIV, na qual esses linfócitos são os principais alvos da infecção pelo vírus 1,13 .…”
Section: Figura 3: Correlação Entre a Carga Viral E Os Resultados Laboratoriais Dos Linfócitos T Cd4 + (A E B) T Cd8 + (C E D) Relação T unclassified
See 2 more Smart Citations
“…Verificou-se que os níveis de linfócitos T CD8 + estavam diretamente relacionados a carga viral e isso deve-se ao importante papel dessas células no combate às infecções causadas por vírus. Portanto, na tentativa de eliminar o vírus, quanto maior a carga viral, maiores serão os níveis detectados dessas células 1,25 . As células T CD4 + , por sua vez, apresentaram uma relação inversamente proporcional com a carga viral, o que pode ser justificada pela história natural da infecção pelo HIV, na qual esses linfócitos são os principais alvos da infecção pelo vírus 1,13 .…”
Section: Figura 3: Correlação Entre a Carga Viral E Os Resultados Laboratoriais Dos Linfócitos T Cd4 + (A E B) T Cd8 + (C E D) Relação T unclassified
“…Tal fato pode ser evidenciado pelo presente trabalho, em que diferenças laboratoriais significativas foram identificadas entre os níveis de linfócitos T CD8 + e T CD45 + na abordagem por sexo. De acordo com o estudo realizado na província chinesa, Yunnan, a partir da análise da contagem de células por sexo, a média dos valores absolutos de linfócitos T CD4 + e linfócitos T CD45 + foram maiores nas mulheres do que nos homens vivendo com HIV/Aids 25,27 . A literatura sobre o comportamento imunológico do HIV entre os diferentes sexos ainda não está totalmente esclarecida.…”
Section: Figura 3: Correlação Entre a Carga Viral E Os Resultados Laboratoriais Dos Linfócitos T Cd4 + (A E B) T Cd8 + (C E D) Relação T unclassified
See 1 more Smart Citation
“…This study also found that CD8 + T cells in the peripheral blood of patients with poor immune reconstitution remained elevated after nutritional treatment, which may be the result of persistent immune activation and inflammatory response caused by microbial translocation (31). In addition, CD8 + T cell counts increased, possibly because CD8 + T cells responded to both viral and intestinal CD4 + T cell depletion, and low CD4/CD8 ratio (< 1), which was not altered by nutritional intervention, promoted an increase in CD8 + T cell counts (32).…”
Section: Discussionmentioning
confidence: 99%
“…The human immunodeficiency virus (HIV) was initially identified in the 1980s in five young men affected by Pneumocystis carinii pneumonia and other opportunistic infections ( 1 ). HIV infection triggers an important immunosuppression condition by disrupting CD4+ T lymphocytes function, leading to a higher risk of developing opportunistic diseases ( 2 , 3 ), especially when CD4+ T cell count falls below than 200 cells/mm3, when the diagnosis of Acquired Immunodeficiency Syndrome (AIDS) is established ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%